Examining infantile facial features and their influence on caretaking behaviors in free-ranging Japanese macaques (Macaca fuscata). - Toshiki Minami; Takeshi Furuichi (PLoS ONE)
Facial features of immature individuals play a pivotal role in eliciting caretaking behaviors in humans. It has been posited that non-human animals share particular infantile facial features with humans, which can elicit caregivers' attention and caretaking behaviors. Nevertheless, the empirical examination of this hypothesis is extremely limited. In this study, we investigated infantile facial features in Japanese macaques (Macaca fuscata), their developmental processes, and their correlation with caretaking and infant behaviors, based on 470 facial photographs from one free-ranging group. We measured the size of facial parts and evaluated these features using non-contact procedures with the animals. The results indicated that, although some partial species differences were observed, the infantile facial features in Japanese macaques were broadly consistent with those previously observed in humans and great apes. Furthermore, half of the infant subjects displayed non-linear developmental trajectories of infantile faces, similar to those suggested in humans. However, unlike previous studies in humans, infantile faces were not significantly associated with maternal or non-maternal caretaking behaviors, nor were their developmental changes correlated with infant behavioral development. These findings indicate that while many aspects of infantile facial features are shared among particular primates, humans may have evolved a uniquely elevated preference for selecting such features among the primate lineage.